Factors Affecting Customer Retention in Commercial Banks In Tanzania; A Case Of Azania Bank Arusha (International Journal of Scientific Research and Management (IJSRM), 2018)
Customer retention is an important element of any banking strategy in today’s increasingly competitive environment. Due to its importance, this study examined factors that affecting customer retention in commercial banks a case of Azania bank, Arusha. The study adopted a case study research design, where data was collected from 132 customers using questionnaires and conducted interviews with employees. The collected data were analyzed using descriptive and inferential statistics mainly frequencies, percentages and mean. One sample t-test, independent t-test, ANOVA, correlation and regression techniques were used to examine the relationships between customer satisfaction, service quality, customer trust, customer commitment, switching barrier factors and customer retention. Correlation results show a positive relationship between service delivery and customer retention, as is the case with customer relationships and customer retention. Therefore, the majority the respondents were ready to continue being a customer at Azania Bank due to the way services are delivered and customer relationships. In addition, regression analysis show that customers treated with respect by bank staff, latest electronic products, and access to banking services anywhere in the country, staff responding promptly to inquiries and valuing customer feedback are significantly influencing customer retention. Therefore, the study concludes that service quality, service delivery, customer relationships and customer satisfaction are positively related to customer retention.